2013
DOI: 10.5507/bp.2013.025
|View full text |Cite
|
Sign up to set email alerts
|

Possible control of paternal imprinting of polymorphisms of the ADAM33 gene by epigenetic mechanisms and association with level of airway hyperresponsiveness in asthmatic children

Abstract: Introduction. ADAM33 is the candidate gene most commonly associated with asthma and airway hyperreactivity (AHR). Aim. The aim of this study was to determine whether level of AHR is associated with certain alleles or haplotypes of the ADAM33 gene in asthmatic children. Methods. One hundred and nine asthmatic children and 46 controls from the general population were examined with spirometry before and after histamine and methacholine inhalation. All subjects were genotyped for single-nucleotide polymorphisms (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The value of T-int >100 is considered as significantly associated as per the Haploview tool. The result supported another study where haplotypes were found to be associated with asthma18; further, these SNPs were associated with an increased predisposition to asthma29, but no such association was found in other studies3031. In another study, rs2853209 SNP was found to be associated with asthma along with T1 (rs2280091) and F+1 SNPs of ADAM33 32.…”
Section: Discussionsupporting
confidence: 73%
“…The value of T-int >100 is considered as significantly associated as per the Haploview tool. The result supported another study where haplotypes were found to be associated with asthma18; further, these SNPs were associated with an increased predisposition to asthma29, but no such association was found in other studies3031. In another study, rs2853209 SNP was found to be associated with asthma along with T1 (rs2280091) and F+1 SNPs of ADAM33 32.…”
Section: Discussionsupporting
confidence: 73%
“…These differences may reflect differences in the cohort composition or methodological differences, including the use of parental reports of asthma as the outcome (vs. wheeze in our studies) and a longer follow-up to 18 years in their study (27). A recent study demonstrated that paternal imprinting of ADAM33, a gene that has been associated with asthma, was associated with the severity of airway hyperreactivity in children with asthma (28), suggesting a parent-of-origin-specific effect. However, this effect was not examined in the context of the child's sex.…”
Section: Discussionmentioning
confidence: 99%
“…This is underlined by sexual dimorphism in study-specific predictors of persistent wheeze demonstrated by effects of paternal asthma for boys 12,[17][18][19][20]23 and minority race (black or Hispanic) for girls. 17 Recent reports of paternal imprinting of ADAM33 47…”
Section: Male Sexmentioning
confidence: 99%
“…This is underlined by sexual dimorphism in study-specific predictors of persistent wheeze demonstrated by effects of paternal asthma for boys 12,[17][18][19][20]23 and minority race (black or Hispanic) for girls. 17 Recent reports of paternal imprinting of ADAM33 47 and sex-specific DNA methylation patterns in the promoter region of zona pellucidabinding protein 2 (ZPBP2) 48 associated with childhood asthma lend credence the sex-specific causal mechanisms. Moreover, our metaregression results suggest that higher risk of Early-Persistent wheezing among male children may be more apparent in high-risk cohorts than in population-based studies.…”
Section: Male Sexmentioning
confidence: 99%